Pengaruh Model Pembelajaran Problem Based Learning terhadap Keterampilan Membaca Kritis Siswa di SD Negeri 5 Kalipucang Kulon - Carissa, Nabila Dian; Zumrotun, Erna; Attalina, Syailin Nichla Choirin (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Critical reading is a process that involves a deep understanding of the information in the reading, but critical reading does not only include understanding the explicit information in the text, but also exploring the hidden meanings that may be hidden behind the words. The low critical reading skills of students are a problem that must be addressed immediately. This study aims to determine the implementation and effect of the PBL model on students' critical reading skills at SD Negeri 5 Kalipucang Kulon. This study uses a quantitative approach with a pre-experimental design. The subjects of the study consisted of 26 students in grade 3, which included 15 boys and 11 girls. The research design used was a one-group pretest and posttest design. The results showed a significance value (p-value) of the normality test for the pretest, which was 0.222, and the posttest was 0.168. In the homogeneity test, the significance value (p-value) is 0.060 > 0.05, which means the data is homogeneous, and the paired sample t-test obtained a significance value (p-value) of 0.001 < 0.05. This proves that the PBL model has a significant effect on students' critical reading skills before and after being given treatment at SD Negeri 5 Kalipucang Kulon.